Mosquito Species (Diptera: Culicidae) Diversity from Ovitraps in a Mesoamerican Tropical Rainforest. Issue 3 (30th January 2018) - Chaverri, Luis Guillermo; Dillenbeck, Claire; Lewis, Devon; Rivera, Cindy; Romero, Luis Mario; Chaves, Luis Fernando
Abstract: Mosquito sampling using efficient traps that can assess species diversity and/or presence of dominant vectors is important for understanding the entomological risk of mosquito-borne disease transmission. Here, we present results from a survey of mosquito species sampled with ovitraps in a neotropical rainforest of Costa Rica. We found the method to be an efficient sampling tool. With a total sampling effort of 29 traps, we collected 157 fourth-instar larvae and three pupae belonging to eight mosquito taxonomic units (seven species and individuals from a homogenous taxonomic unit identified to the genus level). In our samples, we found two medically important species, Sabethes chloropterus (Humboldt) and Trichoprosopon digitatum (Rondani). The former is a proven vector of Yellow Fever in sylvatic environments and the later has been found infected with several arboviruses. We also found that mosquito species abundance and diversity increased with canopy cover and in environments where leaf litter dominated the ground cover. Finally, our results suggest that ovitraps have a great potential for systematic sampling in longitudinal and cross-sectional ecological "semi-field" studies in neotropical settings.